Production of [xi][star] resonances in [sigma]- induced reactions at 345 GeV/c - Adamovič, M. I.; Siebert, Hans-Wolfgang (Arxiv, 1999)
We report on a measurement of the differential and total cross sections of inclusive production of Xi resonances in Sigma - nucleus collisions at 345 GeV/c.
Im Titel werden Xi und Sigma als griechische Buchstaben dargestellt
Im Titel sind "star" und "minus" hochgestellt
Gesehen am 27.02.2020